The role of the sales organization in predicting demand: Qualitative Sales Forecasting - Estampe, Dominique (Henry Stewart Talks, 2010)
Introduction qualitative forecasting, Process of turning experience in forecast Forecasting and new products, Predict changes, Jury of executive opinion, Delphi method, Sales force composite, Qualitative techniques and tools, Salesforce composite forecasting, Salesperson's job, Keys to maximizing value, Summary